Disparities in use modalities among adults who currently use cannabis, 2022–2023 - Meman Diaby; Osayande Agbonlahor; Bethany Shorey Fennell; Joy L. Hart; Delvon T. Mattingly (Journal of Cannabis Research)
Abstract Purpose Following the legalization of cannabis in several U.S. states, the cannabis market has expanded, leading to a wider range of products including smoked, edible, and vape products which have variable health effects. This proliferation highlights the need for more research on patterns of current cannabis use among U.S. adults. Methods We used combined data on adults who currently use (i.e., past 30-day use) cannabis (n = 16,999) from the 2022 and 2023 National Survey on Drug Use and Health. We analyzed whether seven cannabis use modalities including smoking, vaping, dabbing, consuming edibles, taking pills, applying topicals, and absorbing sublingually/orally varied by age, sex, race and ethnicity, sexual orientation, education, income, geographic location, and state medical cannabis laws status by generating weighted proportion estimates and conducting multivariable logistic regression. Additionally, in a subanalysis, we examined differences in blunt use among U.S. adults who reported current cannabis use (n = 12,355), employing similar methods to explore associations with demographic and socioeconomic factors. Results Among adults who currently use cannabis, smoking was the most common cannabis use method (77.33%), followed by edibles (37.31%), vaping (34.75%), dabbing (15.01%), applying topicals (5.93%), absorbing sublingually/orally (4.53%), and taking pills (2.11%). Edibles were popular among adults aged 35–49 years (29.57%), whereas vaping was most common among young adults aged 18–25 years (29.80%). Females (vs. males) had lower odds of smoking cannabis (OR: 0.65; 95% CI: 0.57–0.75) and higher odds of applying topicals (OR: 2.92; 95% CI: 2.23–3.83). Non-Hispanic Black (vs. non-Hispanic White) respondents had higher odds of smoking cannabis (OR: 2.03; 95% CI: 1.51–2.74) and lower odds of consuming edibles (OR: 0.66; 95% CI: 0.56–0.77). Adults aged 50 + years (vs. 18–25) had greater odds of absorbing sublingually/orally (OR: 2.45; 95% CI: 1.59–3.76). In the subanalysis, we found that Non-Hispanic Black (vs. non-Hispanic White) adults had higher odds of blunt use (OR: 5.31; 95% CI: 4.23–6.65). Conclusions Use modality disparities among adults who currently use cannabis highlight the need for tailored public health education and interventions, given the distinct health risks associated with each method of use.